2011
DOI: 10.1111/j.1526-4610.2011.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Manipulations for Cervicogenic Headaches: A Systematic Review of Randomized Clinical Trials

Abstract: The objective of this systematic review was to assess the effectiveness of spinal manipulations as a treatment option for cervicogenic headaches. Seven databases were searched from their inception to February 2011. All randomized trials which investigated spinal manipulations performed by any type of healthcare professional for treating cervicogenic headaches in human subjects were considered. The selection of studies, data extraction, and validation were performed independently by 2 reviewers. Nine randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In addition, a recent systematic review has revealed that existing trials, mostly of good quality, support the effectiveness of manual therapy for chronic tension‐type headache, albeit there were no trials on chronic migraine and chronic cluster headache . At this stage, trials examining the effectiveness of manual therapy for migraine remain limited and of poor quality with conflicting results . Evaluation of the effectiveness and cost‐effectiveness of manual therapies in reducing headache, using sufficiently powered, pragmatic randomized trial designs, should be recognized as a priority for trialists and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent systematic review has revealed that existing trials, mostly of good quality, support the effectiveness of manual therapy for chronic tension‐type headache, albeit there were no trials on chronic migraine and chronic cluster headache . At this stage, trials examining the effectiveness of manual therapy for migraine remain limited and of poor quality with conflicting results . Evaluation of the effectiveness and cost‐effectiveness of manual therapies in reducing headache, using sufficiently powered, pragmatic randomized trial designs, should be recognized as a priority for trialists and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the reviews are inconsistent, since the effectiveness of joint manipulation in tension type headache remains inconclusive; 9 current evidence does not support the use of manipulation for migraine, 10 whereas some positive results have been found for cervicogenic headache. 11 In fact, a review of systematic reviews concluded that the findings reported about effectiveness of spinal manipulation for the management of headaches differed considerably. 12 Further, we observed that the methodological quality of the randomized controlled trials analyzing the effectiveness of spinal manipulation and/or mobilization for headaches is typically low.…”
Section: Scientific Evidence For Manual Therapy In Tension Type and Cmentioning
confidence: 99%
“…77 Controlled trials of spinal manipulation have not demonstrated efficacy in cervicogenic headache or migraine and should not be recommended specifically for the treatment of posttraumatic headache. 78,79 Nerve blocks can be administered for neuralgic pain syndromes, and there are some data that suggest efficacy in cluster, cervicogenic, migraine, and tension-type headache in both adult and pediatric patients. [80][81][82] For refractory headaches acupuncture can be considered, and a recent Cochrane analysis of randomized trials in the treatment of migraine found it to be effective in reducing the frequency of attacks.…”
Section: Management Of Post-concussion Syndromementioning
confidence: 99%